2015
DOI: 10.3748/wjg.v21.i21.6754
|View full text |Cite
|
Sign up to set email alerts
|

True left-sided gallbladder with variations of bile duct and cholecystic vein

Abstract: A left-sided gallbladder without a right-sided round ligament, which is called a true left-sided gallbladder, is extremely rare. A 71-year-old woman was referred to our hospital due to a gallbladder polyp. Computed tomography (CT) revealed not only a gallbladder polyp but also the gallbladder located to the left of the round ligament connected to the left umbilical portion. CT portography revealed that the main portal vein diverged into the right posterior portal vein and the common trunk of the left portal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…In such a case, the cystic duct joins the extrahepatic duct or left hepatic duct from the left side. [7]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In such a case, the cystic duct joins the extrahepatic duct or left hepatic duct from the left side. [7]…”
Section: Discussionmentioning
confidence: 99%
“…[11] There are recent cases where neither the common pre-operative ultrasonography detect the LSG [6], [12], [13] nor the abdominal CT. [5] On the other hand, there are recent cases in which CT revealed LSG[7], [9] an if so, further study such as angiography, CT- angiography or MRI are suggested for a well-organized laparoscopic cholecystectomy [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, preoperative imaging often fails to diagnose LSG as seen in our case. However, there have been reported cases of preoperative identification of a LSG . In these cases, further imaging with magnetic resonance imaging or computed tomography cholangiography is possible to further delineate the anatomy …”
mentioning
confidence: 99%